Lightweight and textured Ni@Cu-encapsulated carbon tube with outstanding electromagnetic interference shielding performance. (29th September 2022) - Huang, Junjun; Sun, Di; Li, Ge; Wang, Xiaoke; Ma, Haodong; Zhang, Wenqing; Chen, Zhenming; Li, Honglin; Gui, Chengmei
Abstract: The low-reflection electromagnetic interference (EMI) shielding material is highly desirable, which would facilitate the reduction of the EM-wave secondary pollution, but classic conflict between performance and density makes it very challenging in practical application. Herein, a textured Ni@Cu-encapsulated carbon tube was designed and fabricated as a conducting material inserted into the middle of polydimethylsiloxane (PDMS) polymer and its application in flexible, light-weight and low-reflection EMI shielding material. Results showed that the active groups on the plant fiber surface could absorb Pd 2+, acting as catalytic center, which can catalyze electroless nickel plating (EP Ni) on its surface by means of textured Ni-encapsulated plant fiber. The inside plant fiber was carbonized and attached to Ni-tube inside surface after annealing, owning to the outstanding heat-conducting capability of Ni coating. To be precise, textured Ni encapsulated C tube was fabricated successfully after annealing at 300 °C. Interestingly, the surface Ni tube could catalyze the EP Cu on its surface by means of textured Ni@Cu-encapsulated carbon tube structure, endowing the composites with efficient dielectric loss and magnetic loss capacity. Combined with PDMS coating, a flexible, light-weight and low-reflection EMI shielding material is fabricated successfully. More importantly, it displays outstanding EMI shielding effectiveness of 35.4 dB, lower reflection one of 0.9 dB, higher specific one of 28.7 dB cm 3 /g, superior flexibility and mechanical properties with a thickness of only 2 mm. This work open a new window for fabricating EMI shielding materials with outstanding EMI shielding performance. Graphical abstract: Image 1 Highlights: A facile process combined with electroless plating and carbonization to fabricate textured Ni@Cu-encapsulated carbon tube for conducting filler of low-reflection electromagnetic interference shielding material was established. The Electromagnetic shielding, flexibility and mechanical properties of as-fabricated material were investigated in detail. It displays lower reflection one of 0.9 dB.